KARAKTERISTIK FISIKOKIMIA EKSTRAK MADU DAN PROPOLIS TRIGONA SP. ASAL LOMBOK UTARA - Nur Nadhifah Zahra; Handa Muliasari; Yayuk Andayani; I Made Sudarma (Jurnal Agrotek Ummat, 2021)
Cultivation of honey and propolis Trigona sp. in the area of North Lombok Regency is growing, but has not equipped with scientific data regarding its physicochemical characteristics. This research aims to determine the physicochemical characteristics of honey and propolis extract of Trigona sp. from North Lombok. Physical parameters measured of the ethanol extract of honey and propolis Trigona sp. includes moisture content and ash content using gravimetric methods; Meanwhile, chemical parameters are identification of compounds using phytochemical screening methods and GC-MS (Gas Chromatography-Mass Spectrometry) instruments. Ethanol extract of honey Trigona sp. has moisture and ash content values of 9.38 ± 0.28% and 1.23 ± 0.02%, respectively; while the extract of propolis Trigona sp. containing water content and ash content of 11.64 ± 0.15% and 1.85 ± 0.02%. Ethanol extract of honey Trigona sp. identified positively containing flavonoid and alkaloid compounds, as well as 16 other compounds identified using GC-MS. Trigona sp. propolis extract contains flavonoids, alkaloids, tannins, saponins, and 10 compounds identified using GC-MS.